Монгол-германы хамтарсан чулуун зэвсгийн судалгааны ангийн 2012 онд хийсэн малтлага судалгааны урьдчилсан үр дүн - Б, Гүнчинсүрэн; Ц, Болорбат; Звинс, Н (Proceedings of the Mongolian Academy of Sciences, 2017)
Mongolian and Germany joint expedition started research excavation at the “Tulbur-16” Paleolithic site in 2012. The excavation covered totally 5 sq.m. In the result of the excavation, there stratigraphic has seven layers and 3664 stone tools are found. The knapping technique of some of the findings are similar to findings from lower layers of Tulbur-4 and Tulbur-15 sites. This result is definitelly indicating that this site belongs to Upper Paleolithic and it is representing that ancient human were settled in this region for longer period: from early to finality of Upper Paleolithic.